A chromosome study and localization of 18S rDNA in Khawia saurogobii (Cestoda: Caryophyllidea) - Orosová, Martina; Marec, Frantisek; Oros, Mikulás; Xi, Bing Wen; Scholz, Tomás (Parasitology research, 2010)
This paper reports results of the first cytogenetic study carried out on a recently described monozoic tapeworm, Khawia saurogobii Xi et al., 2009, from the Chinese lizard gudgeon (Saurogobio dabryi). The karyotype of this species is composed of eight pairs of metacentric and telocentric chromosomes (2n = 16; n = 3m + 5t), metacentric chromosomes representing the first, sixth, and eight pairs. All chromosomes except the largest pair displayed 4',6-diamidino-2-phenylidole (DAPI) positive heterochromatin in centromeric regions. In mitotic preparations stained with Giemsa, one of the homologues of a smaller metacentric chromosome pair (No. 7) showed a distinct secondary constriction, whereas the other did not. Fluorescent in situ hybridization (FISH) with 18S ribosomal DNA (rDNA) probe revealed that the chromosomes No. 7 carry each a cluster of ribosomal genes associated with the centromeric heterochromatin and confirmed that this chromosome pair contains a nucleolar organizer region (NOR). The rDNA-FISH also confirmed heteromorphism in the size of NOR (i.e., secondary constriction) observed after Giemsa staining. The present cytogenetic analysis revealed species-specific characters of K. saurogobii and showed that FISH may represent a new valuable cytogenetic tool suitable for comparative taxonomic or phylogenetic studies within the order Caryophyllidea in the future.
Keywords: Cestoda; Chromosome Mapping; chromozomy; karyotypizace; hybridizace in situ fluorescenční; RNA, Ribosomal, 18S; indoly; ribozomální DNA; heterochromatin; Karyotyping; Nucleolus Organizer Region; Animals; Chromosomes; mapování chromozomů; Heterochromatin; organizátor jadérka; Indoles; zvířata; barvení a značení; In Situ Hybridization, Fluorescence; Staining and Labeling; DNA, Ribosomal; RNA ribozomální 18S; cytogenetické vyšetření; Cytogenetic Analysis